Management of Food Allergy in Children - Utama Wija, Ida Bagus Eka; Sihombing, Jumaini Andriana (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Food allergies represent a significant health challenge in children as they directly impact growth and development. While incurable, the frequency and intensity of allergic reactions can be managed to improve the quality of life. Objective: This study aims to review current management strategies for pediatric food allergies, focusing on prevention and clinical interventions. Method: The research utilizes a systematic literature review of established medical guidelines and clinical trials related to pediatric allergy management. Result and Discussion: Effective management relies on strict allergen avoidance and nutritional counseling to prevent malnutrition. For acute reactions, epinephrine remains the primary first-line treatment, while antihistamines and corticosteroids manage milder symptoms. Emergent therapies such as oral and sublingual immunotherapy show promise in inducing allergen tolerance, though they require strict medical supervision due to potential adverse effects.  Conclusions: Comprehensive management of food allergies involves a combination of strict avoidance, pharmacological preparedness for emergencies, and the potential application of immunotherapy to enhance patient outcomes.